Life in the Moslem East - Ponafidine, Pierre, ?-1919. (Piscataway, NJ)
xiii, [2], 429 sayfa, [41] sayfa resim
Keywords: “Pierre Ponafidine, an Imperial Russian diplomat who served in Ottoman Turkey and Persia, gives a series of studies of certain phases of the life, religion, and customs of people among whom he passed thirty-six years of service“ -- Yayıncı.